2015
DOI: 10.1186/s12876-015-0329-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting post-embolization fever and liver failure after trans-arterial chemo-embolization in a cohort without background infective hepatitis- a prospective analysis

Abstract: BackgroundTransarterial-chemo-embolization (TACE) is used for palliation of unresectable hepatocellular carcinoma (HCC). We studied the tolerability of TACE in a cohort of patients with NASH and alcoholic cirrhosis related HCC.MethodsOf 290 patients with HCC (July 2011 - December 2014), 84 underwent TACE. They were monitored for post-TACE complications: postembolization fever (PEF), nausea and vomiting (NV), abdominal pain, infection, acute hepatic decompensation (AHD) and acute kidney injury (AKI).Results84 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 14 publications
(24 reference statements)
2
19
0
Order By: Relevance
“…This finding was also pointed out in a previous study by Siriwardana et al 2 Another study by Wang et al 18 also showed that female gender correlates with a higher incidence of postprocedural nausea, particularly in premenopausal women. 18 In that study, they found no statistically significant difference in the incidences of nausea and vomiting between male over 50 years and female patients who have entered menopause, a finding that raised the suspicion that these associations could be due to hormonal causes, namely the estradiol level.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This finding was also pointed out in a previous study by Siriwardana et al 2 Another study by Wang et al 18 also showed that female gender correlates with a higher incidence of postprocedural nausea, particularly in premenopausal women. 18 In that study, they found no statistically significant difference in the incidences of nausea and vomiting between male over 50 years and female patients who have entered menopause, a finding that raised the suspicion that these associations could be due to hormonal causes, namely the estradiol level.…”
Section: Discussionsupporting
confidence: 81%
“…These factors were also not related to PES in previous studies. 2,6 The main limitation of our study is its retrospective design. We had to rely on the information of the clinical charts of the patients.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The main complications of TACE are liver failure, acute kidney injury, liver abscess, puncture site bleeding, bone marrow suppression and infection (8,9), all of which occur at a low incidence. HCC patients usually have pre-existing cirrhosis (10,11) and, therefore, have a high incidence of liver dysfunction and portal hypertension, conditions that may cause reductions in white blood cell (WBC) and platelet (PLT) counts.…”
Section: Introductionmentioning
confidence: 99%